STUDY OF SEA SURFACE TEMPERATURE IN INDONESIA ON MONTHLY RAINFALL PREDICTIONS ON AMBON ISLAND - Suryandi Imanuel Sugiarto; Julius Anton Nicolas Masrikat; Simon Tubalawony (Universitas Mataram, 2026)
Ambon Island which is part of the territory of Indonesia has a unique rain pattern. When most parts of Indonesia experience the rainy season, Ambon Island actually experiences a dry season, and vice versa. This study aims to predict rainfall on Ambon Island using sea surface temperature predictors with high correlation. The study was conducted by observing rainfall (CH) data from the Pattimura Ambon Meteorological Station, SPL data with a spatial resolution of 0.25o x 0.25o covering the territory of Indonesia obtained from the European Union's Earth Observation Program (Copernicus) over a period of 30 years (January 1991-December 2020. The results show the Ambon CH Pattern showing Local Patterns and SPL conditions in Indonesia show that in the November-May period Indonesia tends to be dominated by SPL above 28.5oC, SPL warming occurs in southern Indonesia. Meanwhile, in the June-October period, there was a cold SPL movement from southern Indonesia, so that the northern part experienced SPL warming. The highest negative CH and SPL correlation values of 0.57 were in the 15o LS and 135.5o BT regions, while the highest positive correlation values of 0.50 were in the 14.5o LU and 121.25o BT regions. Based on the model built from SPL predictors, the best prediction result is the SPL(+) Model with an RMSE of 227.79.